Vestibular disorders - Lea, Jane; Pothier, David Douglas 1973-2018 (Basel : Karger, 2019)
This collection of articles on the latest developments is written by experts in various sub-disciplines - medical and paramedical - of vestibular disorders. Contributions discuss various manifestations of vestibular disorders and how to diagnose and treat them. The different areas are put into context to support the clinician in the diagnosis and treatment of patients with dizziness, imbalance, and vertigo. New diagnostic tools are presented as are new approaches to the understanding of clinical signs and underlying pathologies. Otolaryngologists seeking to provide up-to-date assessment and care will find this publication a valuable and indispensable read. The contributions presented appeal not only to otolaryngologists of all levels of experience, but also to front-line clinical staff.
Keywords: APARATO VESTIBULAR -- ENFERMEDADES; APARATO VESTIBULAR -- ENFERMEDADES -- DIAGNÓSTICO; APARATO VESTIBULAR -- ENFERMEDADES -- TRATAMIENTO